Aplikasi Ekstrak Kulit Buah Naga Merah (Hylocereus polyrhizus) Pada Pembuatan Susu Kedelai (Hylocereus polyrhizus) - Masyhura MD Masyhura MD; Mhd Iqbal Nusa; Dicky Prasetya (Agrintech: Jurnal Teknologi Pangan dan Hasil Pertanian, 2018)
This study aims to determine the effect of adding extracts of dragon fruit and gum arab fruit to soy milk quality. This research used Factorial Random Design (RAL) with (2) two replications. Factor I is the addition of dragon fruit skin extract password (D) which consists of 4 levels, namely: D1 = 20%, D2 = 40%, D3 = 60%, D4 = 80%.Factor II is the addition of gum arabic concentration with a password (G) consisting of 4 levels, namely: G1 = 0.1%, G2 = 0.2%, G3 = 0.3%, G4 = 0.4%.Parameters observed included protein levels Antioxidants, Ph, organoleptic taste and colors. The result of statistical analysis on each parameter gives the following conclusion: the addition of dragon fruit skin extract gives very significant different effect (P <0,01) to the protein levels antioxidant, Ph, organoleptic taste and  color. The addition gum arab gives very significat different effect (P<0,01) to the protein levels, antioxidant, Ph, organoleptic taste and color.